Aspectos morfoanatômicos e fisiológicos de plantas jovens de amburana (Amburana cearensis (Fr. All. A. C. Smith) e umbuzeiro (Spondias tuberosa Arr. Com.) - Santos, Mayana Matos de Oliveira (2015)
The objectives of this study were to understand the role of the root system of amburana (Amburana cearensis (Fr. All.) AC Smith) and umbuzeiro (Spondias tuberosa Arr. Cam.) In maintaining the initial growth and assimilates partition of seedlings, and determine its contribution to the survival of the species in water restriction situations. For this, studies have been conducted about the early development and dry matter partitioning patterns in the production of seedlings, as well as surveys of their gas exchange, morphological and anatomical aspects, quantification and nature of the compounds stored in the underground system and leaves of young plants submitted to water restriction. For the species under study, preferred drains are the tuberous roots, followed by branches, leaves and lateral roots. Initially, tuberous roots behave as a high activity drain, until it completes its formation. Plants of S. tuberosa showed higher average of the A. cearensis for most of the growth variables, with consequent growth and further development. The results showed interference in the initial plant growth caused by the formation of tuberous root, which is a storage organ. The root system of the species consists of tuberous roots and slender lateral roots. The cross-sections showed that the slender lateral roots have periderm, cortex, vascular cylinder and exchange, and fiber support in both species and secreting structures only in S. tuberous. The cylinder vascular species is polyarc, being endarch and hollow in A. cearensis with obvious pith, and exarco and solid in S. tuberosa. The tuberous roots of species present additional exchanges. The species have adapted to drought, as the opening and closing mechanism of the stomata, water storage mechanism and nutrients in your tuberous roots and osmotic adjustment mechanism. The introduction of young plants of A. cearensis and S. tuberosa can be recommended for restoration programs of degraded areas and forest management.